Virtual Team Role Play Using Second Life for Teaching Business Process Concepts - Rudra, Amit; Jaeger, Bjoern; Aitken, Ashley; Chang, Vanessa; Helgheim, B. (IEEE Computer Society, 2011)
This paper describes the use of a virtual world environment to facilitate a role play assignment for buying and selling Enterprise Resource Planning (ERP) software solutions in a distributed environment. The exercise involved the use of Second Life to facilitate the virtual presentation and meeting among the vendors and the purchaser of the software. Students playing vendors and purchase roles were organized into teams who meet, collaborate, and negotiate business transactions in the virtual environment. The aim of the experiment was to introduce students to properties of ERP-systems which are the most common software systems used by businesses, and at the same time introduce tools for virtual team collaboration in an international setting between students in Norway and Australia. This paper reports the experiences from the students' and teachers' perspectives and we give recommendations regarding the use of Second Life in role-playing exercises.